Adolescent Patella Instability Extensor Mechanics: Insall Extensor Realignment Versus Medial Patellofemoral Ligament Reconstruction. Issue 3 (April 2016) - Edmonds, Eric W.; Glaser, Diana A.
Abstract : Background: A plethora of surgical procedures have been promoted in the literature regarding the treatment of patella instability in the adolescent population; yet, none have compared the joint reaction forces of knee extensor mechanics after extensor mechanism realignment (Insall) or medial patellofemoral ligament reconstruction (MPFLR). The purpose of this study was to determine if there was a difference in knee extensor mechanics between these techniques. Methods: Three cohorts of 10 age-matched adolescents (normal control, Insall, and MPFLR) were compared using preoperative magnetic resonance imaging and postoperative x-ray in the 2 surgical groups. Patella and patella tendon length were measured and the actual moment arm calculated. Compression angles were estimated and the effective moment arms determined. Patellofemoral and quadriceps joint reaction forces were calculated. Comparisons within and between the 3 groups were determined and the dependent variables analyzed for statistical differences. Results: Mean ages (15.6±2.2 y), preoperative measures and dependent variables were not different between the groups ( P >0.05). Postoperatively, there was a significant difference for the patellofemoral joint reaction force with respect to the quadriceps force ( F r / F q ), being larger within the Insall group (1.08±0.08) than the MPFLR group (0.92±0.09) ( P <0.001). The postoperative MPFLR group variables were not significantly different to the control group. In contrast, the postoperative Insall group yielded larger joint reaction forces compared with control (1.08±0.08 vs. 0.83±0.11, P <0.001), as well as different effective moment arms, Insall versus control (51.23±8.8 vs. 41.9±5.9, P <0.001). Conclusions: Not all surgical interventions for recurrent patella instability affect knee mechanics similarly. Although an extensor realignment procedure may still have indications in children, the treating surgeon should be aware that it does not appear to restore normal joint mechanics. Clinical Relevance: The Insall-type procedure may increase the patellofemoral joint reaction forces beyond normal without fully restoring the effective moment arms; whereas, MPFL reconstruction appears to restore the effective moment arm without excessive joint reaction forces.